Corruption and stock market development: new evidence from GCC countries - Mouselli, Sulaiman; Aljazaerli, Moaz Alsherfawi; Sirop, Rasha (Business: Theory and Practice, 2016)
The theoretical relationship between corruption and stock market development has been debated quite extensively in the literature, yet the evidence on the impact of corruption on stock market development remains contradictory and ambiguous. This paper investigates the impact of corruption, as measured by Corruption Perception Index (CPI) published by Transparency International, on stock market development focusing exclusively on Gulf Cooperation Council (GCC) countries with its special characteristics of combining richness with relatively high level of corruption. Results from an estimation of alternative regression models on a panel of six GCC countries over the period 2003–2011, through which CPI is legitimately comparable, confirms a positive impact of corruption on stock market development, where the latter is measured by market capitalization. This is consistent with the view that corruption greases the wheels of economy by expediting transactions and allowing private firms to overcome governmentally imposed inefficiencies.